Programming and problem solving with C++ - Dale,Nell (Nell B.); Weems, Chip; Richards, Tim (Computer scientist) (Massachusetts: Jones & Bartlett Learning, 2023)
'Programming and Problem Solving with C++ is appropriate for the introductory C++ programming course at the undergraduate level. Due to its coverage, it can be used in a one or two semester course. Competitive advantages of this title include: The reputation of the authors Appropriate and thorough coverage of C++ topics for the beginner programmer Clear examples and exercises, with hands-on examples and case studies'--
Includes bibliographical references and index.
Buku bacaan asas fakulti
Keywords: C++ (Computer program language)